Participation of Farmers in Resource Management Activities at Selected Haor Areas in Netrokona District (Journal of the Bangladesh Agricultural University, 2020)
Resources in haor region in Bangladesh are underutilized and need to be managed for better outcomes which may significantly improve the livelihoods of the haor people. Thus, the study was undertaken mainly to determine the extent of participation of farmers and identify the factors influencing the farmers’ participation in resource management activities. The study was conducted at four unions under Mohanganj upazila (Sub-district), Netrokona district. One hundred farmers were interviewed through personal interview using a pre-tested interview schedule during April, 2019. Participation of farmers in resource management activities was the focus variable and nine selected characteristics of the respondents constituted the explanatory variables. Both descriptive and inferential analyses were used to analyze the collected data. The highest proportion (89 percent) of the respondents belonged to medium and low participation category while only 11 percent of them belonged to high participation category. Building embankment, land preparation for crop cultivation, preparing manures were the activities where most of the farmers participated. Level of education, family size and knowledge on resource management were identified as influential factors that affect the participation of the farmers as confirmed by regression model. Besides, among 13 identified problems, lack of training occupied first position followed by lack of good governance, lack of cold storage where these two problems secured second and third ranked position respectively. Respective authorities such as Department of Agricultural Extension (DAE), Department of Fisheries (DoF), Department of Livestock Services (DLS), NGOs etc. should take initiatives for instance organize training, provide support system, motivation etc. for improving the socioeconomic conditions of the haor farmers.J Bangladesh Agril Univ 18(3): 717–723, 2020https://doi.org/10.5455/JBAU.106978